Capital utilization for livelihoods among rural fishing migrant households in the origin area - Meekaew, Nattapon; Ayuwat, Dusadee (International Journal of Engineering and Technology, 2018)
This research paper aims to analyze the capital utilized for livelihoods among the fishing migrant households in the origin area. A qualitative methodological approach, specifically a phenomenological approach was applied in the study, with in-depth interview and participatory observation employed as research tools. Twenty fishing migrant households, located in Bah sub-district, Surin province were selected as the target of the study; the data collection period was during January to June 2017. The research results explored the variety of capital that the fishing migrant households utilized for their livelihoods. The households created their livelihood strategies based on the capital they possessed. The five categories of capital that were identified as resources for creating livelihood strategies included 1) financial capital, which the households used to make life choices in the form of savings and land accumulation, 2) human capital, which was in the form of knowledge and experience applied in their careers in order to sustain the household life. 3) Social capital, which was used to solve household problems, for instance, tracking household members who were missing during fishing work, or participating in community activity, and 4) natural capital and physical capital, which were used as a mechanism in striving to make a living, for instance, collecting wild food items, or using natural materials to construct a house.Â